2016
DOI: 10.1016/j.ultsonch.2016.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the adhesion strength of micro electroforming layer by ultrasonic agitation method and the application

Abstract: Micro electroforming is widely used for fabricating micro metal devices in Micro Electro Mechanism System (MEMS). However, there is the problem of poor adhesion strength between micro electroforming layer and substrate. This dramatically influences the dimensional accuracy of the device. To solve this problem, ultrasonic agitation method is applied during the micro electroforming process. To explore the effect of the ultrasonic agitation on the adhesion strength, micro electroforming experiments were carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…This is due to the effect of microbubbles explosion from the supercritical CO 2 affects nucleation growth during the electrodeposition. Notably, the observed diffraction pattern in US-SC-CO 2 -15 W cm −2 displays the most significant full width at half maximum (FWHM), which indicated that ultrasonic agitation would lead to the smallest grain size [16] , [23] , [24] . Similar to the previous reports, the grain sizes are calculated from the Scherrer equation [38] , [39] , [40] , [41] , [42] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is due to the effect of microbubbles explosion from the supercritical CO 2 affects nucleation growth during the electrodeposition. Notably, the observed diffraction pattern in US-SC-CO 2 -15 W cm −2 displays the most significant full width at half maximum (FWHM), which indicated that ultrasonic agitation would lead to the smallest grain size [16] , [23] , [24] . Similar to the previous reports, the grain sizes are calculated from the Scherrer equation [38] , [39] , [40] , [41] , [42] .…”
Section: Resultsmentioning
confidence: 99%
“…In recent decades, ultrasonic-assisted electrodeposition has been widely used to improve the quality of electrodeposited materials [22] , [23] , [24] . It is due to the fact of high energy from the ultrasonic irradiation that creates cavitation effects such as mass transport processes, acoustic streaming, surface activation, and micro jetting formation [25] .…”
Section: Introductionmentioning
confidence: 99%
“…The poor coating layers will exfoliate and create serious effects during the tissue healing process. The coating pieces will leave the surface due to poor strength and affect the surrounding body parts [86,87]. The coating on metallic substratesis widely used to make it bio-compatible and bio-active.…”
Section: Existing Challenges In Coating For Metallic Biomaterialsmentioning
confidence: 99%
“…Weak interface bonding can even lead to the warpage or delamination of electrodeposited layers and nally result in the fabrication failure. At present, many methods have been adopted to improve the adhesion strength, including surface activation prior to plating [8], regulating electrodeposit current density [9] and ultrasound-assisted electrodeposit method [10]. However, post-processes, photoresist removal and sacri cial layer release, also have great effects on the interfacial bonding strength, which are rarely investigated.…”
Section: Introductionmentioning
confidence: 99%